Particle dean migration in short arcuated microchannels - Ishaq Idrus Khan Surattee (Nanyang Technological University, 2021)
Inertial microfluidics is a high throughput cell separation technique based on size- based particle inertial focusing effects. While Dean flow in curvilinear geometries such as spiral or serpentine channels have been well studied, Dean-induced particle migration in short arcuated channel length has not been explored. In this study, inertial migration of fluorescent microparticles in short arcuated microchannels was investigated experimentally. The effect of channel length (< 5 cm) for half loop and one loop channels, radii (3.5 mm, 5 mm & 8 mm) and flow rates (Reynolds number 50 – 200) on particles migration were characterized. With the same channel length and flow conditions, particle migration distance was the largest for the channel with the smallest radius (smallest Dean number), which indicates the presence of stronger Dean vortices to induce particle lateral migration. Interestingly, comparison between half loop channel and one loop channel at the same downstream distance showed that bead migration distance was greater in the one loop channel, which suggests that the backpropagation of pressure gradient from downstream flow towards upstream Dean vortices may alter their strength and resultant particle lateral migration. Taken together, our results confirm the presence of Dean-induced particle migration in short curvilinear channels where these channel geometries can be further developed for inertial-based particle sorting and facilitate channel multiplexing to achieve higher throughput.